Multi-informant assessment of Cognitive Disengagement Syndrome (formerly Sluggish Cognitive Tempo). Self-reported measures of children in relation to parents - Cano-Crespo, Almudena; Moreno-García, Inmaculada; Servera, Mateu; Morales-Ortiz, Manuel (Anales de Psicología / Annals of Psychology, 2024)
The aim was to examine, using a multi-informant approach, parent and child measures of Cognitive Disengagement Syndrome (CDS) and their relationship with internalising and externalising symptoms. 279 children (9-13 years old) and their parents completed assessments of the CDS, the inattention of Attention Deficit Hyperactivity Disorder (ADHD), and other internalising and externalising measures. The items of the three measures of CDS converged reasonably well on the CDS factor. Discriminant evidence of validity of the relationships between test scores and the measures of the three different constructs (CDS, loneliness and preference for solitude) was provided. A stronger association was found between parental assessment of the measures of CDS with anxiety and depression and between inattention with hyperactivity/impulsivity and oppositional defiant disorder. The predictive ability of the measure of CDS on self-reported measures of loneliness and preference for being alone was observed. A possible association was found between parent-rated CDS measure and children's gender and age. In conclusion, the data support the inclusion of self-reported measures in assessing CDS. Measures of CDS in children are linked to other internalising measures and inattention to externalising measures.